Trade Effects of Services Trade Liberalization in the EU - Joseph F. Francois; Olga Pindyuk; Julia Woerz (FIW - Research Centre International Economics, 2008)
This paper gives a quantitative assessment of possible trade effects resulting from different trade liberalization scenarios within the EU. The simulations are based on the GTAP model, a computable general equilibrium model. We use the GTAP database and own estimates of protection in the service sector. We compare different scenarios, which differ in the extent of their liberalization (linear versus sector country and specific cuts in existing trade barriers, including all sectors versus only selected sectors). Our findings point towards larger gains from more comprehensive cuts (i.e. including all service sectors) and larger gains for the - up to date more restricted - new EU members.
Keywords: C68; F13; F17; 330; export of services; trade liberalization; computable general equilibrium modelling; services trade